The Effectiveness of Social-Emotional Learning Strategies and Mindful Breathing with Biofeedback on the Reduction of Adolescent Test Anxiety - McLeod, Carolyn; Boyes, Mike (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
Educational programs that incorporate social emotional-learning (SEL) strategies, study skills, and mindful breathing using biofeedback can help adolescents decrease worry and social stress, increase test preparedness self-efficacy, and improve academic performance due to lowered levels of test anxiety. The current study examined the efficacy of a SEL intervention (implemented into a high school psychology course) focused on study skills and mindful breathing and its impact on student attitude and behavioural changes (e.g., test anxiety, self-efficacy), academic performance, and physical changes. A quasi-experimental explanatory mixed methods study conducted at a rural Alberta high school examined pre- and post-intervention results between two groups of Grades 9–12 students (N = 105) with one group receiving the intervention (mindful breathing sessions, emotional regulation techniques, study and test-taking skills, and coping strategies) while the other received regular programming. Quantitative data included a Test Anxiety Survey (TAS), Student Opinion Survey–Short Form (SOS-SF), and reading comprehension (RC) tests to measure attitude and behavioural changes, followed by qualitative data obtained from student semi-structured interviews and focus groups for further interpretation. Quantitative results from repeated-measures (RM) ANOVAs indicated significant increases in self-efficacy for preparation and test-taking, increased academic achievement, decreased worry about future social stress, and increased positive affect. Effect sizes for significant impacts ranged from .45 to .65. Qualitative data indicated that students acquired new SEL strategies to help them handle stressful test situations more effectively. The current study addresses topics of interest to educators (e.g., test anxiety, social emotional learning) with a discussion of applications for extension and development of the program in junior and senior high classrooms.